2018
DOI: 10.1097/mol.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Classical and alternative roles for autophagy in lipid metabolism

Abstract: Purpose of review Intracellular lipid metabolism is a complex interplay of exogenous lipid handling, trafficking, storage, lipolysis, and export. Recent work has implicated the cellular degradative process called autophagy in several aspects of lipid metabolism. We will discuss both the classical and novel roles of autophagy and the autophagic machinery in this setting. Recent findings The delivery of lipid droplets to lysosomes for hydrolysis, named lipophagy, was the first described functional role for aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 60 publications
2
58
0
Order By: Relevance
“…Interestingly, the lipid profile of cultured Atg7 deficient keratinocytes is also altered compared controls, but the change in the proportions of the lipid classes examined in that study (sterols, FFA, and TG) is quite different to those which we find in sebum. This once again demonstrates that the effects of autophagy inhibition with regard to lipid metabolism is very context dependent, as has been demonstrated on numerous occasions (see for instance Refs ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, the lipid profile of cultured Atg7 deficient keratinocytes is also altered compared controls, but the change in the proportions of the lipid classes examined in that study (sterols, FFA, and TG) is quite different to those which we find in sebum. This once again demonstrates that the effects of autophagy inhibition with regard to lipid metabolism is very context dependent, as has been demonstrated on numerous occasions (see for instance Refs ).…”
Section: Discussionsupporting
confidence: 78%
“…Apart from other growth factor‐mediated mechanisms which lead to SG enlargement, such as direct effects of Epigen, an Nrf2 target gene, EGFR or amphiregulin, alterations of lipolysis, lipogenesis and/or lipid metabolism are also possible pathways, and autophagy has been implicated in the first two of these processes, as well as in lipoprotein trafficking (reviewed recently in Ref. ). In addition, Pparγ, a lipid‐activated nuclear transcription factor, plays an important role in sebum production, sebaceous gland differentiation and lipid metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the initiation of autophagy is commonly associated with lipid droplet inclusion into autophagosomes and subsequent degradation by lysosomes (lipophagy) [ 54 , 55 ]; however, in this study an accumulation of lipid droplets was observed. The small guanosine triphosphatase Rab7 is indispensable for lipophagy [ 56 ] and is associated with lipid droplets and lysosomes under starvation conditions [ 57 ]. When Rab7 is silenced, there is an accumulation of lipid droplets [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This product is then actively exported out of lysosomal compartment through Niemann-Pick-type C1 protein. Several lysosomal proteins such as acid sphingomyelinase (ASM), mucolipin-1, and H + -ATPase regulate metabolism and transport of cholesterol in lysosomes [62].…”
Section: Lipid Metabolismmentioning
confidence: 99%